SIR2 is required for polycomb silencing and is associated with an E(Z) histone methyltransferase complex. - Furuyama, T.; Banerjee, R.; Breen, T.R.; Harte, P.J. (Current Biology, 2004)
SIR2 was originally identified in S. cerevisiae for its role in epigenetic silencing through the creation of specialized chromatin domains. It is the most evolutionarily conserved protein deacetylase, with homologs in all kingdoms. SIR2 orthologs in multicellular eukaryotes have been implicated in lifespan determination and regulation of the activities of transcription factors and other proteins. Although SIR2 has not been widely implicated in epigenetic silencing outside yeast, Drosophila SIR2 mutations were recently shown to perturb position effect variegation, suggesting that the role of SIR2 in epigenetic silencing may not be restricted to yeast.Evidence is presented that Drosophila SIR2 is also involved in epigenetic silencing by the Polycomb group proteins. Sir2 mutations enhance the phenotypes of Polycomb group mutants and disrupt silencing of a mini-white reporter transgene mediated by a Polycomb response element. Consistent with this, SIR2 is physically associated with components of an E(Z) histone methyltransferase complex. SIR2 binds to many euchromatic sites on polytene chromosomes and colocalizes with E(Z) at most sites.SIR2 is involved in the epigenetic inheritance of silent chromatin states mediated by the Drosophila Polycomb group proteins and is physically associated with a complex containing the E(Z) histone methyltransferase.